NUMERICAL SIMULATION OF THE IMPACT OF WATER-AIR FRONTS ON RADIONUCLIDE PLUMES IN HETEROGENEOUS MEDIA - Aquino, J.; Francisco, A. S.; Pereira, F.; Amaral Souto, H. P. (Revista de Engenharia Térmica, 2006)
The goal of this paper is to investigate the interaction of water-air fronts with radionuclide plumes in unsaturated heterogeneous porous media. This problem is modeled by a system of equations that describes both water-air flow and radionuclide transport. The water-air flow problem is solved numerically by a mixed finite element combined with a non-oscillatory central difference scheme. For the radionuclide transport equation we use the Modified Method of Characteristics (MMOC).We present results of numerical simulations for heterogeneous permeability fields taking into account sorption effects.